Never-resting microglia: physiological roles in the healthy brain and pathological implications - Amanda Sierra (Frontiers Research Topics, 2015)
Microglia are largely known as the major orchestrators of the brain inflammatory response. As such, they have been traditionally studied in various contexts of disease, where their activation has been assumed to induce a wide range of detrimental effects. In the last few years, a series of discoveries have challenged the current view of microglia, showing their active and positive contribution to normal brain function. This Research Topic reviewed the novel physiological roles of microglia in the developing, mature and aging brain, under non-pathological conditions. In particular, this Research Topic discussed the cellular and molecular mechanisms by which microglia contribute to the formation, pruning and plasticity of synapses; the regulation of adult neurogenesis as well as hippocampal learning and memory; among other important roles. Because these novel findings defy our understanding of microglial function in health as much as in disease, this Research Topic also summarized the current view of microglial nomenclature, phenotypes, origin and differentiation, and contribution to various brain pathologies. Additionally, novel imaging approaches and molecular tools to study microglia in their non-activated state have been discussed. In conclusion, this Research Topic sought to emphasize how the current research in neuroscience is challenged by never-resting microglia.